2022
DOI: 10.5114/wiitm.2022.119585
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous ablation for adrenal metastases: a systematic review and meta-analysis.

Abstract: Introduction: Imaging-guided percutaneous ablation (PA) is commonly employed for the treatment of patients diagnosed with adrenal metastasis (AM), but comprehensive analyses are essential to validate the efficacy and safety of this approach. Aim: The present meta-analysis was designed to evaluate the safety, efficacy, and long-term outcomes associated with the imaging-guided PA treatment of AM. Material and methods: Relevant studies in the PubMed, Embase, and Wanfang databases published as of June 2022 were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The adrenal glands are a major site of metastasis in patients with tumors of the lungs, liver, colon, kidneys, and other organs [1][2][3]. Non-small-cell lung cancer (NSCLC) is a highly prevalent primary tumor type often characterized by adrenal metastasis (AM), with NSCLC as the primary tumor type in 13-58% of AM patients [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adrenal glands are a major site of metastasis in patients with tumors of the lungs, liver, colon, kidneys, and other organs [1][2][3]. Non-small-cell lung cancer (NSCLC) is a highly prevalent primary tumor type often characterized by adrenal metastasis (AM), with NSCLC as the primary tumor type in 13-58% of AM patients [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports, however, have indicated that adrenalectomy can improve AM patient overall survival (OS), with a post-surgery median OS of 23-30 months [5,6]. Together with the design of mini-invasive therapeutic techniques, imaging-guided ablation strategies have successfully been utilized to treat AM [2][3][4]. Liu et al [1] additionally determined that imaging-guided ablation and adrenalectomy can achieve comparable OS for AM lesions under 5 cm in size.…”
Section: Introductionmentioning
confidence: 99%